2013
DOI: 10.1111/jdv.12239
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of onychomycosis in psoriatic patients: a systematic review

Abstract: We systematically reviewed all available literature concerning the prevalence of onychomycosis in patients with nail psoriasis and the distribution of pathogens causing onychomycosis in this specific group of patients. Databases searched were Pubmed, EMBASE and the Cochrane Controlled Clinical Trial Register. All studies reporting on the prevalence of onychomycosis in nail psoriasis were obtained, and quality assessment was determined by the STrengthening the Reporting of OBservational studies in Epidemiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 43 publications
3
68
0
16
Order By: Relevance
“…Based on our results, the most plausible scenario explaining the high recorded frequency of onychomycosis among nail psoriasis patients seems to be the increased susceptibility of their nails to colonisation by pathogens, such as yeast and moulds, which tend to invade non‐healthy nails . These types of fungi rely on the altered structure and defective defence mechanisms of psoriatic nails to cause infection . Bigger observational studies, preferably cohort studies, will be able to further elucidate the two diseases’ relationship as well as establish causality.…”
Section: Discussionmentioning
confidence: 81%
“…Based on our results, the most plausible scenario explaining the high recorded frequency of onychomycosis among nail psoriasis patients seems to be the increased susceptibility of their nails to colonisation by pathogens, such as yeast and moulds, which tend to invade non‐healthy nails . These types of fungi rely on the altered structure and defective defence mechanisms of psoriatic nails to cause infection . Bigger observational studies, preferably cohort studies, will be able to further elucidate the two diseases’ relationship as well as establish causality.…”
Section: Discussionmentioning
confidence: 81%
“…In addition to that, when the studies were examined individually, only three of them could conclude that their patients with nail psoriasis have a significant higher possibility to develop onychomycosis compared to healthy controls. The remaining seven studies found no significant differences, although many of them showed a trend to a higher prevalence of onychomycosis in patients affected by psoriasis with nail involvement …”
Section: Should We Distinguish the Two Diseases Or Should We Prove Thmentioning
confidence: 92%
“…Recently, Klaassen et al . reviewed all the available literature concerning the prevalence of onychomycosis in patients with and without nail psoriasis. Only 10 studies met the inclusion criteria.…”
Section: Should We Distinguish the Two Diseases Or Should We Prove Thmentioning
confidence: 99%
“…The group identified that the major area where prevalence reviews were disparate was in their conduct of critical appraisal or quality assessment of included studies. For example, whilst some reviews used instruments that were appropriate for reviews of prevalence data (9,10), others used instruments or criteria not designed to critically appraise studies reporting prevalence (such as reporting guidelines, study design specific tools, or self-developed criteria for their review question) (11)(12)(13), or refrained from conducting a formal quality assessment altogether (14,15). Therefore, the working group sought to address this gap by developing and testing a critical appraisal form that could be used for studies included in systematic reviews of prevalence data.…”
Section: Introductionmentioning
confidence: 99%